2012
DOI: 10.1109/tpami.2012.17
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Retrieval of Articulated Geometry Models

Abstract: Abstract-Due to the popularity of computer games and animation, research on 3D articulated geometry model retrieval is attracting a lot of attention in recent years. However, most existing works extract high dimensional features to represent models and suffer from practical limitations. First, misalignment in high dimensional features may produce unreliable Euclidean distances and affect retrieval accuracy. Second, the curse of dimensionality also degrades efficiency. In this paper, we propose an embedding ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Bronstein et al [28] directly compute the distance between two non-rigid shapes by formulating the Gromov-Hausdorff distance as a multidimensionalscaling-like continuous optimisation problem. Tam and Lau [29] showed that manifold learning can be used to improve the shape retrieval accuracy of existing methods.…”
Section: Related Workmentioning
confidence: 99%
“…Bronstein et al [28] directly compute the distance between two non-rigid shapes by formulating the Gromov-Hausdorff distance as a multidimensionalscaling-like continuous optimisation problem. Tam and Lau [29] showed that manifold learning can be used to improve the shape retrieval accuracy of existing methods.…”
Section: Related Workmentioning
confidence: 99%
“…A number of recent works have successfully applied this framework for various purposes in mesh processing and analysis, including [Sun et al 2009;Ovsjanikov et al 2010;Mémoli 2011] who study the kernel arising from a converging mesh Laplacian operator on a surface, leading to the definition of diffusion distances on a mesh and an isometric one-point matching technique. It has also been used to determine symmetry , for co-segmentation [Sidi et al 2011] and for retrieval [Tam and Lau 2012].…”
Section: Spectral Analysismentioning
confidence: 99%
“…There are also feature descriptors for shape matching in articulated (or non‐rigid) model retrieval and in finding similar parts of models . Gal and Cohen‐Or used salient geometric features for partial shape matching and similarity.…”
Section: Related Workmentioning
confidence: 99%